Moment Method Analysis of Radiation and Scattering by Thin Wires in an Infinite Dissipative Medium - Fleming, A.H.J. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this report, a modified version of AMP (Antenna Modelling Program), a forerunner of NEC (Numerical Electromagnetics Code), is validated for applications involving thin wire structures immersed in an infinite dissipative medium. A Pascal derivative of MiniNEC2, the Mini Numerical Electromagnetics Code, is also used to provide numerical comparison as needed when other data are not available. Computations from both programs are compared with analytical and pre-existing experimental results. Drive point impedances, currents and near fields for a range of thin wire radiators and scatterers are presented. Useful results are obtained for the highest conductivity case tested and for less conductive media, agreement of computed parameters with available comparative data of approximately 10% or better is achieved.